In vitro models of the metastatic cascade: from local invasion to extravasation - Bersini, S. (2013)
A crucial event in the metastatic cascade is the extravasation of circulating cancer cells from blood capillaries to the surrounding tissues. The past 5 years have been characterized by a significant evolution in the development of in vitro extravasation models, which moved from traditional transmigration chambers to more sophisticated microfluidic devices, enabling the study of complex cell–cell and cell–matrix interactions in multicellular, controlled environments. These advanced assays could be applied to screen easily and rapidly a broad spectrum of molecules inhibiting cancer cell endothelial adhesion and extravasation, thus contributing to the design of more focused in vivo tests.